Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
ThanhNghiem

Gi ải các phương trình sau
a)x-3(2x-6)=21-(5x+3)
b)(x-2)(x+2)-(x-1)2=2(x+1)
c)\(\dfrac{9x+4}{6}\)=1-\(\dfrac{3x-5}{9}\)

d)\(\dfrac{6x+1}{x^2-7x+10}\)+\(\dfrac{5}{x-2}\)=\(\dfrac{3}{x-5}\)

Nguyễn Lê Phước Thịnh
26 tháng 1 2024 lúc 13:21

a: \(x-3\left(2x-6\right)=21-\left(5x+3\right)\)

=>\(x-6x+18=21-5x-3\)

=>18=18(luôn đúng)

=>\(x\in R\)

b: \(\left(x-2\right)\left(x+2\right)-\left(x-1\right)^2=2\left(x+1\right)\)

=>\(x^2-4-x^2+2x-1=2x+2\)

=>2x-5=2x+2

=>-7=0(vô lý)

=>\(x\in\varnothing\)

c: \(\dfrac{9x+4}{6}=1-\dfrac{3x-5}{9}\)

=>\(\dfrac{3\left(9x+4\right)}{18}=\dfrac{18}{18}-\dfrac{2\left(3x-5\right)}{18}\)

=>3(9x+4)=18-2(3x-5)

=>27x+12=18-6x+10

=>27x+12=-6x+28

=>33x=16

=>\(x=\dfrac{16}{33}\left(nhận\right)\)

d: ĐKXĐ: \(x\notin\left\{2;5\right\}\)

\(\dfrac{6x+1}{x^2-7x+10}+\dfrac{5}{x-2}=\dfrac{3}{x-5}\)

=>\(\dfrac{6x+1}{\left(x-2\right)\left(x-5\right)}+\dfrac{5}{x-2}=\dfrac{3}{x-5}\)

=>\(6x+1+5\left(x-5\right)=3\left(x-2\right)\)

=>6x+1+5x-25=3x-6

=>11x-24=3x-6

=>8x=18

=>\(x=\dfrac{9}{4}\left(nhận\right)\)

vovanquy
26 tháng 1 2024 lúc 20:29

a: x−3(2x−6)=21−(5x+3)

=>x−6x+18=21−5x−3

=>18=18(luôn đúng)

=>x∈R

b: (x−2)(x+2)−(x−1)2=2(x+1)

=>x2−4−x2+2x−1=2x+2

=>2x-5=2x+2

=>-7=0(vô lý)

=>x∈∅

c: 3(9x+4)18=1818−2(3x−5)18

=>3(9x+4)=18-2(3x-5)

=>27x+12=18-6x+10

=>27x+12=-6x+28

=>33x=16

=>6x+1x2−7x+10+5x−2=3x−5

=>x=94(nhận)


Các câu hỏi tương tự
Mochi _sama
Xem chi tiết
Nguyễn Linh
Xem chi tiết
Nguyễn Linh
Xem chi tiết
ThanhNghiem
Xem chi tiết
Trần Ngọc Anh Thư
Xem chi tiết
Tuyet Anh Lai
Xem chi tiết
Lưu huỳnh ngọc
Xem chi tiết
Nguyễn Linh
Xem chi tiết
Tuyết Ly
Xem chi tiết